Educating the concept of local food and culinary of a destination through social media websites and mobile applications / Mohd Hairi Jalis, Jefry Elias and Mohd Nazri Ibrahim - Jalis, Mohd Hairi; Elias, Jefry; Ibrahim, Mohd Nazri (Universiti Teknologi MARA, 2021)
Social media websites and mobile applications significantly play an important role in today’s modern society worldwide, especially sharing and providing knowledge regarding local food and culinary concept of a place or destination. Nevertheless, choosing incorrect or sharing unclear online material, including videos and photographs, as content in social media websites and mobile applications will mislead the actual facts and confuse the viewers/users. Within the qualitative research approach, this paper has gathered related videos and photographs to specifically analyse how those materials posted on social media were utilised to educate viewers/users about a place or destination of local food and culinary concept. It was found that geographical indication is seen as the most crucial information in educating people about local food and culinary concept of a particular place or destination. This is followed by social background and history. Moreover, social background details through the unique food production process and eating style, at the same time, enable people to have a better understanding of the story of the local food and culinary. In conclusion, this study suggests serious and careful attention in planning and editing videos as well as capturing and selecting images in photographs considered crucial to be posted and shared as content in social media websites and mobile applications. This helps reduce people’s doubt on the information accuracy and encourages social media website viewers’ or mobile application users’ interest/passion to learn about local food and culinary concept of a place or destination.